Clinical diagnosis of bacterial vaginosis - Salvador, Manuel (2015)
Study achieved At Rioja City, Department of San Martin during the mouths of January to August 1995, in, a sample of 120patients who had vaginal discharge Bacterial vaginosis was present in 78% of women with active sex life with ages betwen 21 and 35 years old. It is more frequent in women who have 2 or more children 90% and incidence was 32,8%. Amsel's criteria permits clinical diagnosis of bacteria vaginosis in 75 to 92% of cases.